Characterising wind shear exponents in the offshore area using Lidar measurements. (October 2022) - Yan, B.W.; Li, Q.S.; Chan, P.W.; He, Y.C.; Shu, Z.R.
Abstract: From a practical standpoint, the 1/7th power law has been extensively used for wind speed extrapolation in wind energy community. However, numerous studies have suggested that unrestricted use of the 1/7th power law can be sometimes misleading due to the highly variable nature of wind shear. Hence, the main goal of this study is to unveil the wind shear characteristics at an offshore site using 3-yr wind Lidar measurement data. The calculation indicates that more than 80% of wind shear exponents (WSEs) are less than 0.14, and the occurrence of negative WSE is more frequent than those over-land. The mean value of WSE increases with wind speed, while the variance exhibits a decreasing pattern. The seasonal variability of WSE is apparent, with a maximum in April and a minimum in September and October. Likewise, the WSE varies within a diurnal cycle, in which higher values are often observed in night-times, while lower and almost constant values are found during daytime. In addition, the effect of atmospheric stability on WSE is also evident, with larger mean values obtained in near-neutral and stable conditions.